PENGARUH KOMUNIKASI, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA DI PT. BAKRIE METAL INDUSTRIES - Firdha Fahrun Nisa; Rivera P Sukma (Human Capital Development, 2017)
Purpose- The major problem in managing employee is compensation scheme. This study aims to determine the independent variable communication, motivation, and compensation to the dependent variable of employee performance in PT. Bakrie Metal Industries. Design/methodology/approach- The study was conducted by using quantitative descriptive technique. The population in this study are employees of the production and engineering departement in PT. Bakrie Metal Industries as much as 232 employees with a sample of 147 using the slovin formula. The sample used in nonprobability sampling with accidental sample technique. The test results were analyzed with multiple linear regression method using SPSS Statistics 20. The analysis technique used includes of test the validity and reliability, the classic assumption test in the form of normality test, multicollinearity, heteroscedasticity test, multiple linear regression analysis and hypothesis testing in the form of test f, t-test, correlation (R) and the coefficient of determination (R2). Findings- The results showed that unsignificant difference between the communication to performance of employee, motivation have significant effect on performance of employee, and compensation have significant effect on customer satisfaction in PT. Bakrie Metal Industries.